Radial distribution of Ni in stemwood of Quercus ilex L. trees grown on serpentine and sandy loam (umbric leptosol) soils of NE-Portugal - Nabais, C; Freitas, H; Hagemeyer, J; Breckle, S W (Plant and soil, 1996)
Concentrations of Ni were determined in xylem and phloem of Quercus ilex trees growing on serpentine and sandy loam soils of northeast Portugal. Radial distribution patterns of Ni in stemwood were compared to variations in annual growth increments of the trees. Concentrations of Ni in xylem and phloem were higher in Q. ilex from serpentine soil, when compared with Q. ilex of a sandy loam soil. The radial distributions of Ni showed large variations among the trees, although they all grew in the same area within a short distance from each other. These differences can be caused by small-scale spatial variations in the soil. Therefore, the use of such radial Ni distributions for a retrospective biomonitoring of the Ni pollution of larger areas appears questionable.
Keywords: dendrochemistry; Nickel; Quercus ilex; serpentine; tree rings